Synthesis and Characterization of Montmorillonite Membrane for Nickel and Zink Metals Filtration in Electroplating Liquid Waste - Hidayah, I. (Indonesian Journal of Chemistry and Environment, 2020)
The application of ceramic membrane technology has been applied in water treatment. The montmorillonite used was analyzed by XRD and showed typical montmorillonite peaks at 2Î¸ 7.49o, 28.07o, 35.75 o, 40.73o, 49.14o dan 67.03o. Montmorillonite membrane was made by the process of dry pressing.PVA in montmorillonite is expected to function as a binder agent. The result variation on PVA composition 0%, 1%. 2%, 3% and 4%, show the flux value that increased with the adition of PVA composition. The montmorillonite membrane with a 4% PVA composition a result greatest flux and porosity values compared to other compositions. The resulting flux value is 1596.5679 L/m2.h and porosity 20.9477%. SEM-EDXtest result showed montmorillonite membrane is a porous membrane that is spread and evenly distributed but the resulting pore is not uniform. Montmorillonite membrane rejection of nickel metal was 55.5352% dan zink metal was 37.8614% with a 40-minute filtration process.